Tanggungjawab Grab Express Terhadap Konsumen Dalam Jasa Pengantaran Barang - Yulianti, Wa Ode; Berlianty, Teng; Haliwela, Nancy Silvana (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Grab Express is a goods delivery service provided by the Grab company for people in Indonesia, grab express offers services to consumers in the form of services with drivers/couriers as business partners of the Grab Indonesia company. However, the services provided by the grab express company still have various irregularities committed by drivers/couriers to consumers who use grab express services.Purposes of the Research: This study aims to identify and describe the legal relationship between Grab Express and consumers in goods delivery services and this research also aims to analyze and explain accountability in the event of a loss on the part of the consumer.Methods of the Research: This research is a normative legal research, using a law approach and a conceptual approach. Legal research materials include primary, secondary, tertiary data sources. Data collection techniques in the form of literature study. Techniques for analyzing data on legal materials that were collected and compiled systematically and then reviewed and analyzed qualitatively.Results of the Research: From the research results, companies that provide Grab Express services can be held responsible for damage to goods sent to consumers through the driver/courier. Responsibility can be realized in the form of compensation and replacement as a result of damage or loss of goods experienced by consumers. The legal relationship between Grab Express and consumers occurs when consumers agree to the Grab Express service application. Grab Express has a legal relationship with the driver/courier as the officer who will deliver the goods to the consumer. If there is damage, the responsibility for the consumer can be requested from Grab Express and followed up by the driver/courier. Grab Express and driver/courier parties in carrying out their business activities are required to carry out their work responsibly and not harm consumers. Consumers are obliged to receive services as a form of right because they have fulfilled their obligations by paying a fee for using the Grab Express service.